Experimental Study on the Mechanical Properties of the Fiber Cement Mortar Containing Polyurethane - Xijun Zhang; Hongyuan Fang; Mingrui Du; Mingsheng Shi; Chao Zhang (Advances in Materials Science and Engineering)
Polymer is a kind of high molecular elastic material. The polymer cement mortar composite material formed by mixing it with cement mortar has the advantages of light weight, high strength, and good durability compared with traditional mortar materials. The effect of polyurethane polymer content on mechanical properties and microstructure of polyvinyl alcohol (PVA) fiber cement mortar was studied by compressive test, flexural test, and SEM analysis. The test results show that as the content of polyurethane increases, the compressive strength gradually decreases, and the flexural strength gradually increases. The addition of polyurethane helps to optimize the microstructure of PVA mortar, improve the compactness of the material, and enhance the bending resistance of the mortar. The mechanical properties of materials obtained from the experiment can provide references for engineering applications.